Child sexual abuse reported by adult survivors - Ring, Sinéad.
1 online resource
Keywords: Child Sexual Abuse Reported by Adult Survivors is a wide-ranging and timely critical history and analysis of legal responses to historical' or non-recent' child sexual abuse (NRCSA) in England and Wales, Ireland and Australia, each of which represents an evolving and progressive approach to this important and complex issue. The book examines the emergence of NRCSA as a distinctive social, political and legal phenomenon in each country and explores the legal responses developed to address its unprecedented challenges. Courts and parliaments in each country have reformed existing doctrine and practice andhave created new ways of holding state and private actors accountable and new ways of addressing survivors' injuries. Criminal law, tort law, public inquiries and state reparations have all been to the forefront of these new legal responses, which have transformed law's engagement with NRCSA survivors and understandings of justice itself. However, despite this undeniable progress, the book identifies ways in which the legal responses developed in each country fail to deliver accountability and recognition to NRCSA survivors and argues thatsuch failures betray the law's inherent ambivalence to delivering justice for these survivors. Creating new insights into legal responses to this complex contemporary legal, social and political problem, this book will be of great interest to academic lawyers, political scientists and historians, as well as those working on related topics in criminology, sociology, social policy, cultural studies and gender studies.